The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1136/bjsports-2017-098932
|View full text |Cite
|
Sign up to set email alerts
|

Does MRI add value in general practice for patients with traumatic knee complaints? A 1-year randomised controlled trial

Abstract: NTR3689.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A large Netherlands-based multi-centre, non-inferiority randomized control trial (TACKLE Trial ¼ TraumAtic Complaints of the Knee -Leiden University Medical Center (LUMC) and Erasmus MC Trial) provides new evidence that GP MRI referrals (356 patients aged 18-45 years) for traumatic knee complaints following clinical pathways resulted in neither worse nor better outcomes than usual care for quality-oflife knee-related daily function during a 1-year follow up. 27 Our study shows decisions for specialist referral and appropriate intervention are improved when guidelines were consistently followed. The TACKLE Trial could be seen as a difference in management of operative versus non-operative care, rather than the role of MRI in outcomes.…”
Section: Comparison With Existing Literaturementioning
confidence: 77%
See 1 more Smart Citation
“…A large Netherlands-based multi-centre, non-inferiority randomized control trial (TACKLE Trial ¼ TraumAtic Complaints of the Knee -Leiden University Medical Center (LUMC) and Erasmus MC Trial) provides new evidence that GP MRI referrals (356 patients aged 18-45 years) for traumatic knee complaints following clinical pathways resulted in neither worse nor better outcomes than usual care for quality-oflife knee-related daily function during a 1-year follow up. 27 Our study shows decisions for specialist referral and appropriate intervention are improved when guidelines were consistently followed. The TACKLE Trial could be seen as a difference in management of operative versus non-operative care, rather than the role of MRI in outcomes.…”
Section: Comparison With Existing Literaturementioning
confidence: 77%
“…Their inclusion criteria of generalised knee complaint due to trauma or sudden onset adds weight to the use of specific condition clinical guidelines, such as those used in our study. Kisser et al 12 and the TACKLE Trial team 27 both emphasise the importance of radiologist involvement in decision-making; something that our trial encouraged and was well-received by GPs.…”
Section: Comparison With Existing Literaturementioning
confidence: 79%
“…24 Another trial found that adding MRI in primary care for younger patients with traumatic knee complaints did not improve knee-related function after one year. 33 These studies show that adding imaging tests that are known to yield high rates of structural asymptomatic findings to the care pathway of musculoskeletal disorders do not translate into better patients' outcomes. It can contribute to overdiagnosis and overuse of subsequent treatments such as surgery.…”
Section: Trials Linking Diagnostic Tests To Patients' Outcomesmentioning
confidence: 99%
“…An interesting finding of the previous trials was that physicians and patients mostly preferred the use of the advanced imaging techniques and were more satisfied with their care although patients' outcomes were not improved. 27,33 This situation poses a real challenge for clinicians. Conceptual models propose that receiving a diagnostic label may have physical, psychosocial and financial consequences as well as increasing treatment burden, exposure to unnecessary tests and treatments and adverse events that lead to dissatisfaction with care.…”
Section: Prognosis-rarely Used But As Equally Importantmentioning
confidence: 99%